(untitled) (Damascus University Journal for the economic and Political sciences, 2024)
Fraud exists in all insurance phases as of issuance until compensation assessment and payment of claims, and it considered one of moral hazard in insurance, this hazards may occur because of the sole liability of the insured person or by the assistance of other parties from the company or from outside. The research herein aim to measuring and identifying different forms of fraud in insurance market, then identifying its causes. The researcher relies on different statistical techniques to test hypotheses such as Multiple Regression Analysis, Factor Analysis and Man Whitney Test. The researcher has been able to design a proposed system to manage fraud in insurance companies that can cover all insurances phases and its parties and identify the mechanisms for confronting fraud in insurance markets especially in medical insurance branch.